2021
DOI: 10.3390/ma14123363
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sewage Sludge Content and Sintering Temperature on Selected Properties of Lightweight Expanded Clay Aggregate

Abstract: Wastewater treatment processes produce sewage sludge (SS), which, in line with environmental sustainability principles, can be a valuable source of matter in the production of lightweight expanded clay aggregate (LECA). The literature on the influence of SS content and sintering temperature on the properties of LECA is scarce. This paper aims to statistically evaluate the effects of SS content and sintering temperature on LECA physical properties. Total porosity, pore volume, and apparent density were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…Sludge had a water content of 5%, which was slightly higher compared to pineapple peel at 2%. reason was the forces between solid particles in the sludge, such as Van der Waal's force, hydrogen chains, valence bonds, and electrostatic force [28]. Furthermore, tapioca starch had a higher density because of amylose and amylopectin molecules.…”
Section: Effect Of Adhesives and Briquette Composition On Density And...mentioning
confidence: 99%
“…Sludge had a water content of 5%, which was slightly higher compared to pineapple peel at 2%. reason was the forces between solid particles in the sludge, such as Van der Waal's force, hydrogen chains, valence bonds, and electrostatic force [28]. Furthermore, tapioca starch had a higher density because of amylose and amylopectin molecules.…”
Section: Effect Of Adhesives and Briquette Composition On Density And...mentioning
confidence: 99%
“…In Europe, the most popular bedding materials are straw, wood carvings, or sawdust, but in the USA, the most recommended bedding material is sand, which unquestionably elevates the ash content, as Nam et al reported the ash content of dairy cattle manure with sand bedding to be 48.8 ± 3.1% [78]. High ash content positions animal manure closer to sewage sludge than plant-origin biomass [79][80][81][82].…”
Section: Ash Contentmentioning
confidence: 99%
“…En cuanto a la composición, para lograr una adecuada expansión de los agregados, la materia prima debe contener componentes que liberan gases cuando se descomponen. En simultáneo se debe alcanzar un estado piroplástico que, por la presión de dichos gases, produzca la expansión de los agregados (González-Corrochano, et al, 2009;Latosinska et al, 2021;Moreno-Maroto et al, 2020;Korat et al, 2013). La producción de agregados porosos a partir de materia prima que contiene minerales arcillosos e impurezas como óxido de hierro, materia orgánica y carbonatos, presenta diversas fuentes de generación de gas a altas temperaturas: la liberación de moléculas de agua entre láminas y la deshidroxilación de los minerales arcillosos, la disociación o reducción de óxidos férricos, la combustión de materia orgánica, y la descomposición térmica de carbonatos (Ayati et al, 2018).…”
Section: Introductionunclassified